1989
DOI: 10.1088/0268-1242/4/12/001
|View full text |Cite
|
Sign up to set email alerts
|

MOS interface states: overview and physicochemical perspective

Abstract: The metal-oxide-semiconductor (MOS) transistor has become the dominant device for very large-scale integrated circuits. The performance and reliability of an MOS device are heavily influenced by the quality and properties of the interface between the oxide and the Si region directly beneath. Inherent, process-related, and operationally and environmentally generated interface states or traps are exceedingly harmful or disabling when present. Although controlled successfully by semiempirical design, fabrication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
103
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(114 citation statements)
references
References 44 publications
10
103
0
1
Order By: Relevance
“…24 In the case of a silicon ͑111͒ orientation, it is widely accepted to be a trivalent silicon center ("SiwSi 3 ) located at the interface, where the dangling bond is located perpendicular to the silicon/ oxide plane. 23 For the Si͑111͒-SiO 2 interface, the DOS distribution across the energy gap demonstrates two clear peaks in the lower and upper portions of the energy gap. The precise energy levels of the peaks in the DOS distribution vary slightly with the characterization method used.…”
Section: Discussion: Origin Of Interface Statesmentioning
confidence: 92%
See 1 more Smart Citation
“…24 In the case of a silicon ͑111͒ orientation, it is widely accepted to be a trivalent silicon center ("SiwSi 3 ) located at the interface, where the dangling bond is located perpendicular to the silicon/ oxide plane. 23 For the Si͑111͒-SiO 2 interface, the DOS distribution across the energy gap demonstrates two clear peaks in the lower and upper portions of the energy gap. The precise energy levels of the peaks in the DOS distribution vary slightly with the characterization method used.…”
Section: Discussion: Origin Of Interface Statesmentioning
confidence: 92%
“…Using the EPR method it has been shown that for unpassivated Si-SiO 2 interfaces the majority of the measured interface states are silicon atoms with dangling bond ( P b ) orbitals. 23 The technique most commonly used to dissociate the hydrogen from the Si-SiO 2 interfacial defects is vacuum annealing (1ϫ10 Ϫ6 Torr) at temperatures in the vicinity of 700°C. An alternative technique is to rapidly ͑Ͻ1 s͒ pull the wafers following a conventional furnace oxidation.…”
Section: Discussion: Origin Of Interface Statesmentioning
confidence: 99%
“…Исследования этих явлений для достаточно толстых (более 5 нм) слоев SiO 2 проводятся уже бо-лее 40 лет [2], и к настоящему времени развиты до-статочно полные представления о механизмах прояв-ляющихся эффектов [3][4][5][6]. Разработка наномасштабных электронных устройств стимулировала изучение повре-ждения тонких, и в особенности сверхтонких (толщиной менее 4 нм), изолирующих пленок.…”
unclassified
“…͑2͒ The energy spectrum of dangling-bond defects exhibits two peaks 4 ͑3͒ Subsequent to the passivation of dangling bonds with H, the reduction of the interface state density in the upper part of the semiconductor band gap ͑acceptors͒ should be equal to that of states in the lower part of the band gap ͑donors͒. Our experiments clearly show that this is not the case in SiC/SiO 2 , 2,3 while Fukuda et al present no data for p-type SiC.…”
mentioning
confidence: 99%